Spatial distribution and association of biophysical factors with chickpea chlorotic stunt and pea seed-borne mosaic viruses affecting legume crops in Ethiopia - Ademe, Anteneh; Kumari, Safaa; Alemu, Tesfaye; Abraham, Adane; Aynewa, Yetsedaw; Moukahel, Abdulrahman; Guadie, Demsache; Kemal, Seid Ahmed (Wiley: 12 months, 2023)
Food legumes are key commodities produced in sole and mixed cropping system in Ethiopia. Their productivity has been affected recently by virus infections. Field surveys were conducted from 2018/19 to 2021/22 cropping seasons in the highlands of Ethiopia to identify major viruses and determine how biophysical factors affect disease incidence. A total of 2797 samples of chickpea (755), lentil (1683), fenugreek (111) and grass pea (248) were collected from 194 farmers' fields in Amhara (North Shewa, South Wollo and East Gojjam zones) and Oromia (East Shewa, West Shewa and North Shewa zones) regions. Laboratory testing using Tissue blot immunoassay showed that chickpea chlorotic stunt virus (CpCSV, genus Polerovirus, family Solemoviridae) and pea seed-borne mosaic virus (PSbMV, genus Potyvirus, family Potyviridae) were the major viruses affecting legume crops in Ethiopia. The highest relative virus incidence of CpCSV (90.6%) and PSbMV (11.5%) was recorded in samples of chickpea and lentil crops, respectively. Except for crop conditions, all the independent variables significantly affected PSbMV incidence, whereas all independent variables showed a highly significant association (p < .0001) with CpCSV Incidence. A CpCSV incidence of ≥30% had a high probability of association with chickpea and fenugreek crops, the presence of aphid vectors and the 2018/19 cropping season. Similarly, PSbMV with an incidence ≥7% was highly associated with the 2018/19 cropping season. Both viruses can be managed by the combined application of cultural practices, insecticide's application, healthy seeds and resistance breeding.